141 Polyvinylpyrrolidone-Coated Catheters Show Fewer Astrocytes and Choroid Plexus Epithelium Adhesion and Better Flow/Pressure Performance Than Other Commercial Catheters in a New Catheter Assay System. (April 2023) - Chan, Alvin; Ruiz, Leandro; Lee, Seunghyun; Shah, Vaibhavi; Muhonen, Michael
Abstract : INTRODUCTION: The major cause of failure of cerebral spinal fluid (CSF) shunting devices in pediatric patients is proximal catheter occlusion. There are a number of shunt catheters commercially available, but their occlusion properties are unclear. METHODS: There were four catheters tested: 1) antibiotic-impregnated, 2) polyvinylpyrrolidone, 3) barium stripe, and 4) barium impregnated. Catheters were inoculated with cultured astrocytes or choroid cells and incubated in growth media for 7 days prior to testing. Sample catheters were placed into a 3D-printed ventricular replicating system to test occlusion properties. Artificial CSF was pumped through the system to mimic physiologic flow and pressure resistance sensors measured obstruction. Afterward testing, catheters were stained with anti-GFAP or anti-transthyretin to visualize cellular adhesion using a fluorescence microscope. RESULTS: Five catheters of each type were used. Polyvinylpyrrolidone catheters had the highest flow (e.g., least obstruction) in the ventricular replication system (0.12 mL/min) compared to the antibiotic coated (0.10 mL/min), barium stripe (0.02 mL/min) or barium impregnated (0.08 mL/min; p < 0.01). Polyvinylpyrrolidone catheters showed the lowest median cell attachment after cell marker staining (<1 cells per 0.07 mm 2 ) compared to antibiotic coated (4.0 cells per 0.07 mm 2 ), barium stripe (3.5 per 0.07 mm 2 ) or barium impregnated (2.0 per 0.07 mm 2 ). CONCLUSIONS: Polyvinylpyrrolidone catheters were least likely to be occluded by astrocytes or choroid cells during testing in a novel ventricular replicating system due to lower cellular adhesion. Our findings may have clinical significance when choosing proximal ventricular catheters that are least likely to occlude and prevent proximal shunt failure.